FUNDAMENTALS OF STANDARDIZATION OF INNOVATION ASSESSMENT IN PUBLIC HEALTH PROMOTION PROGRAMS - Vasil'eva,; Konovalov ,; Zudin,; Smbatyan ,; Vasil'ev ,; Yakushin, (Revista Inclusiones, 2020)
Health technology assessment is the focus of public health experts and the global community. The public health promotion programs at any level are integrated organizational technology (innovation project) that can be covered by the general requirements of the HTA (health technology assessment) formulated by EUnetHTA (European Network for Health Technology Assessment), but they need to be specified for different types of technologies. The latter is the purpose of the study. Results and discussion. Considering public health promotion Programme from the viewpoint of the system approach methodology as a complex organizational technology justified the need to use a multicriteria approach (Multi-criteria decision analysis, MDA) to assess it. The methodology was developed on the basis of data from the content analysis of literature and regulatory and methodological materials using the method of expert assessments. It provides a comprehensive quantitative assessment of the Programme, which can contribute to the objectification of support for management decisions for increasing its innovation and, accordingly, ensuring the strategy of innovative development of health care in the region. Conclusion. Assessment of the value of the Programme should take into account the status of all its components, state of their spatial and temporal characteristics, the ability to achieve targets of public health improvement, the real usefulness and efficiency of the Program.